Juvenile justice a reference handbook - Shoemaker, Donald J. (Contemporary world issues, 2016)
"Authoritative, current, and easy to use, this book is an outstanding resource for readers looking to gain an accurate and thorough understanding of American juvenile justice. Presents historical and contemporary data in an easy-to-understand fashion that survey the complex history of the juvenile justice system and allow readers to better comprehend the key issues Includes a perspectives chapter that enables readers to hear voices from individuals with different backgrounds who are concerned with juvenile justice Provides an ideal resource for general readers who want to learn more about the history and current events concerning juvenile justice as well as students without previous background knowledge of the subject Contains a chronology of key moments in the history of juvenile justice in the United States as well as a glossary of key terms and definitions to guide the reader"-- Provided by publisher.